JURIDICAL REVIEW OF THE IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY (CSR) AS A BANKING COMMITMENT TO REALIZING SUSTAINABLE BANKING (CASE STUDY AT PT BANK BJB, TBK) - Abubakar, Lastuti; Handayani, Tri (Varia Justicia, 2018)
Applicability of the Financial Services Authority Regulation (POJK) No. 51 of 2017 on Sustainable Finance will gradually require banks to apply the principles of sustainable finance. One of the banking commitments to realize sustainable banking is carried out through the implementation of social and environmental responsibility (CSR) that integrates economic, social, environmental and governance aspects. The legal issue in implementing CSR is the change like regulation, which is all voluntary rules to become obligatory rules. Also, banking CSR practices require adjustments to accommodate sustainable financial principles to realize sustainable banking. The approach method used in this study is a normative juridical approach with descriptive, analytical research specifications, using secondary data in the form of primary, secondary and tertiary legal materials analyzed qualitatively juridically. The results of the study indicate that the regulations governing CSR as a commitment of banks to realize sustainable banking still require more detailed arrangements, specifically the determination of the amount and source of CSR funds and sanctions for violations of CSR. Also, banks have not been optimal in using CSR as a means to accelerate the realization of sustainable banking. The effort that must be made by banks is to include CSR as part of the company's value and change the view that CSR is a good practice of banking that will generate long-term benefits for all stakeholders.